2015
DOI: 10.4103/0975-7406.168018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of a new polyherbal formulation against paracetamol and D-galactosamine induced hepatic toxicity

Abstract: Objective:The present study was envisaged to evaluate the protective effect of polyherbal formulation, DRDC/AY/8060, developed by Dabur India Ltd., against paracetamol and D-galactosamine induced hepatic toxicities in Wistar rats.Materials and Methods:The study was carried out in two different experiments of 10 and 14 days against paracetamol and D-galactosamine, respectively. Animals were divided into different treatment groups (n = 6). The control group received normal saline, a toxicant group in two experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
3
1
Order By: Relevance
“…The PNE in group III ameliorated the altered enzyme levels; which contrasts the observations of Khan et al. [45] and Amin et al. [47] , who found the minimal inflammation and normal lobular architecture in the livers of treated rats.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The PNE in group III ameliorated the altered enzyme levels; which contrasts the observations of Khan et al. [45] and Amin et al. [47] , who found the minimal inflammation and normal lobular architecture in the livers of treated rats.…”
Section: Discussioncontrasting
confidence: 90%
“…Elevated liver enzymes in response to different drugs have been observed in several animal models [43] , [44] . A formulation containing the aerial parts of P. niruri has been shown to ameliorate the toxic effects of paracetamol and d -galactosamine [45] and to reduce CCl 4 -induced hepato-renal toxicity [46] . In a thioacetamide-induced liver cirrhosis Sprague Dawley rat model, P. niruri treatment improved liver biochemical parameters, reduced oxidative stress enzyme and lipid peroxidation levels along, and restored histological and morphological patterns in livers [47] , as well as in diabetic rats [48] .…”
Section: Discussionmentioning
confidence: 99%
“…D-galactosamine (GalN) is known as a hepatotoxic chemical agent. 50 D-galactosamine increased serum hepatic marker enzyme activities (AST, ALT, alkaline phosphatase, and γ-glutamyl transpeptidase) and the lipid peroxidation and decreased the antioxidant capacity of the plasma and liver. It was observed that CH decreased hepatic enzyme activities and lipid peroxidation products, such as TBARS, lipid hydroperoxides, and conjugated dienes, and increased the activities of free radical–scavenging enzymes, such as SOD, CAT, GPx, GR, GST, and the levels of GSH, vitamin C and vitamin E in the liver.…”
Section: Methodsmentioning
confidence: 96%
“…Even though the activity of the body increased due to metabolic and circulatory alterations occur when the tissues are damaged (Ma, 2004). Polyherbal formulation contains the andrographolide in steam and leaves which show the anti‐hepatotoxic activity and also reduces the level of CCL4‐induced hepatic enzymes (Khan et al ., 2015). Flavone and flavonoid concentrates present in polyherbal formulation give hepatoprotective property which maintain the level of serum glutamate pyruvate transaminase, alkaline phosphatase, serum glutamate oxaloacetate transaminase, and direct and indirect bilirubin (Gupta et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%